2019
DOI: 10.1111/ene.13884
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous thrombolysis in wake‐up stroke: real‐world data from the Austrian Stroke Unit Registry

Abstract: Background and purpose Data on real‐world experience with intravenous thrombolysis (IV tPA) in wake‐up stroke (WUS) are limited. The aim of this study was to examine the efficacy and safety of IV tPA in patients with WUS included in the Austrian Stroke Unit Registry. Methods Data from a large nationwide stroke unit registry including initial stroke severity, vascular risk factors, comorbidities, treatment with IV tPA, symptomatic intracerebral haemorrhage (sICH) and functional outcome were extracted and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…However, real-world data from the nationwide Austrian Stroke Unit Registry compared in a non-randomized study the safety and efficacy of IVT in WUS and known onset of symptoms in stroke patients. There was no statistical difference regarding clinical outcome and complication rate [10]. These registry data do not fully reveal the selection parameters for IVT in these patients.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…However, real-world data from the nationwide Austrian Stroke Unit Registry compared in a non-randomized study the safety and efficacy of IVT in WUS and known onset of symptoms in stroke patients. There was no statistical difference regarding clinical outcome and complication rate [10]. These registry data do not fully reveal the selection parameters for IVT in these patients.…”
Section: Introductionmentioning
confidence: 56%
“…Compared with this, the WAKE‐UP trial showed a rate of sICH of 2% , whereas in the EXTEND trial sICH occurred in 6.2% . Data from the Austrian Stroke Unit Registry comparing WUS with stroke patients with known symptom onset presented a rate of sICH of 4.1% .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Eight studies [22–29] used noncontrast CT (NCCT) scanning as the primary determinant of candidacy for IV tPA, and two studies [30,31] used CT perfusion imaging. Five studies [4,5,32–34] used MRI, whereas one study [35] included a large sample of patients from multiple centers that used multiple types of imaging strategies. In all, the 16 studies (two RCTs and 14 observational studies) included a total of 14,017 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Mean patient ages were reported in 13 studies [4,5,22,24,26–34] and ranged from 63.9 to 78 years. Median patient ages were reported in three studies [23,25,35] and ranged from 69 to 75 years. Stroke severity in the treated groups, as measured by median NIHSS score, ranged from 5 to 11.9, and thus the included studies reported data for patients with primarily moderate stroke severity.…”
Section: Resultsmentioning
confidence: 99%